Experimental testing of wire finned heat exchanger coated with aluminium fumarate MOF material for adsorption desalination application. (1st February 2022) - Saleh, Majdi M.; Elsayed, Eman; AL-Dadah, Raya; Mahmoud, Saad
Highlights: Aluminium fumarate coated heat exchanger was developed. Operating conditions were investigated through an experimental parametric study. Performance of aluminium fumarate coated and packed systems were compared. Aluminium fumarate coated system outperformed packed one in adsorption desalination. Abstract: Adsorption technology can supply both cooling and drinking water without using electricity as it can be operated using solar energy or waste heat sources. Commercially available adsorption systems utilize adsorbent porous materials such as zeolite and silica gel that suffer from high regeneration temperature for the former and lower hydrophilicity of the latter. To avoid these problems, aluminium fumarate metal-organic framework (MOF) material is used in this study as a promising new adsorbent material with water uptake higher than that of silica gel and zeolite. The material was integrated as a coated layer instead of the conventional granular form. The performance of the developed coated wire wound finned tube heat exchanger was compared with packed one using aluminium fumarate in adsorption cooling and desalination applications. Results showed that the performance of the coated heat exchanger outperformed the packed heat exchanger for both applications. For adsorption water desalination, the coated wire finned heat exchanger produced a specific daily water production (SDWP) of 23.5 m 3 /ton/day compared to only 12.7 m 3 /ton/day for packed heat exchanger. For adsorption cooling application, the coated wire finned heat exchanger produced a specific cooling power (SCP) and a coefficient of performance (COP) of 682 W/kg and 0.32 compared to 318.5 W/kg and 0.23 for packed heat exchanger.